â€œHumanities to Humanoidsâ€: Edutainment of Artificial Intelligence through Ict - Suseebharathi, T; I. Ajit, Dr (International Journal of Engineering and Technology, 2018)
Era of technology has bestowed with plethora of developments and evolution in the routine human life. One field in which such changes could be experienced much is the genre of films. In the recent past, there are myriads of films released with the concept of AI (Artificial Intelligence). The globe of AI, is often an interesting topic for the engineering graduates but it is not focused by the students pursuing graduation in Humanities. The objective of this research critique is to bring out how AI could be introduced in humanities classrooms using films. Attempt is made to justify the objective using a few films as examples.Â